Evaluation of single-use reprocessed laparoscopic instrument sterilization (Revista Latino-Americana de Enfermagem, 2011)
This experimental, comparative, laboratory study evaluated the effectiveness of the sterilization of single-use laparoscopic instruments - SULIs (grasper, dissector, scissors, Veress needle and electrosurgical probe system), after contamination-challenge with bacterial spores and sheep blood, and compared the results of the sterilization tests with those of the equivalent reusable instruments. The cleaning methods used were; ultrasonic washer with pulsatile water jet and enzymatic detergent, manual cleaning, cleaning with pressurized water and rinsing. The SULIs were sterilized with ethylene oxide and the reusable instruments in an autoclave. Sterility tests showed 100% negative results for recovery of contaminate microorganisms in both groups. It was concluded that, regarding the sterilization, that it is possible to reprocess SULIs.